(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2025)
Introduction. The war launched against Ukraine by the Russian Federation on February 24, 2022, has become the largest military conflict in the European space since World War II. Military operations cause great damage to the environment. Direct hits of shells, burnt military equipment and oil products destroy the ecosystem and pollute soils and water with heavy metals and toxic elements. Purpose. The purpose of the article is a comprehensive study of lands disturbed as a result of hostilities, and a set of works on the restoration and use of disturbed territories is proposed. Methods. The methodological basis of the study is the theoretical provisions of science, scientific works of famous scientists in the field of use of disturbed lands. To solve the research tasks in the work, statistical, monographic methods, logical analysis and a systematic approach were used. Results. The article analyzes the main negative consequences of hostilities. Information data on the presence of toxic heavy metals in soils after bombings and artillery shelling is provided. The main set of works for the restoration of the damaged territory is proposed. Conclusions. The result of the study was the discovery that a quick solution to the current situation with the contamination of territories as a result of the war of the Russian Federation against Ukraine at the state level is possible only if effective regulatory legal acts and institutions are developed and applied. One of the first conditions is the development and approval at the legislative level of the National Program for the Protection and Restoration of Lands in Ukraine in the Post-War Period, which should include a detailed plan for the restoration of the lands of Ukraine.